External Iliac Artery Laceration Caused by Hip Prosthesis Migration - Diogo Lino Moura; Mário Moreira; Luís Antunes; Alfredo Gil Agostinho; Manuel Fonseca; António Albuquerque (Revista Brasileira de Ortopedia, 2019)
Abstract Hip arthroplasty is a common and safe intervention in orthopedic surgery. However, the proximity of this joint to large vessels makes the occurrence of vascular injury a rare but serious and possibly lethal complication of this surgical technique. Acute vascular injuries in the context of a hip arthroplasty have variable etiologies and clinical presentations, and are more common in revision surgeries and in situations of medial intrapelvic migration and of chronic infection of the hip prosthesis. In the present article, the authors present a case of acute and late major vascular complication in the context of hip arthroplasty revision. The patient developed an acute laceration of the external iliac artery caused by chronic and progressive medial intrapelvic acetabular migration of the hip prosthesis associated with chronic infection.